Penyuluhan Pemanfaatan Media Sosial untuk Memperluas Jangkauan Pasar di Kampung Mayangsari Kelurahan Kalipancur Kota Semarang - Taufiq Andre Setiyono; Mekani Vestari; Muhammad Yusuf; Muliawan Hamdani; Setyo Pantawis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
Kampung Tematik is one of the innovations launched by the Government of Semarang City. Kampung Tematik are part of the sub-district that are undergoing repairs. Mayangsari Village, which is located in Kalipancur sub-district, Semarang City, is one of the kampung Tematik with superior products like of river tubbings and snacks. This community service aims to provide counseling on the use of social media to expand market reach in Mayangsari Village. The method used is by means of socialization to local residents. Through this counseling, it is hoped that the people of Mayangsari Village can promote local residents' production snacks as well as the beauty of river tubing and promote the Mayangsari Village area as one of the kampung Tematik in Semarang City. This devotion is carried out by socializing to public in Mayangsari Village, Kalipancur sub-district, Semarang City. The result is all entrepreneur expected to being able to expand market reach in Mayangsari Village, Kalipancur sub-district, Semarang City.